2015
DOI: 10.1111/1365-2745.12343
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐scale variation of fungal‐endophyte incidence in temperate grasses

Abstract: Summary1. The strength of many interactions between plants and other organisms changes across regional gradients. For example, the relevance of plant-herbivore interactions increases with primary production. Likewise, biotic interactions collectively become more intense from the poles to the equator. Yet, the regional variation of the interaction between grasses and systemic fungal endophytes, which provide resistance to biotic and abiotic environmental factors (i.e. herbivory and drought), is poorly understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 70 publications
(192 reference statements)
4
40
0
Order By: Relevance
“…Both Jensen et al (2011) and the present study found grass species of tundra to hold a range of fungal endophyte taxonomic units (also by the culture method), suggesting that latitudinal patterns are dependent on the type of species of the host plant. Still, even among grass host species, low colonization frequency of Epichlo€ e endophytes at higher latitudes have been found (Semmartin et al 2015), indicating latitudinal patterns are likely also dependent on type of endophytic species. As demonstrated in the present study, fungal endophytes are both common at high latitude and are affected by tundra ecosystem processes.…”
Section: Discussionmentioning
confidence: 99%
“…Both Jensen et al (2011) and the present study found grass species of tundra to hold a range of fungal endophyte taxonomic units (also by the culture method), suggesting that latitudinal patterns are dependent on the type of species of the host plant. Still, even among grass host species, low colonization frequency of Epichlo€ e endophytes at higher latitudes have been found (Semmartin et al 2015), indicating latitudinal patterns are likely also dependent on type of endophytic species. As demonstrated in the present study, fungal endophytes are both common at high latitude and are affected by tundra ecosystem processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the incidence of fungal endophytes was positively correlated with mean annual precipitation in populations of Bromus setifolius, another palatable grass occurring in southernmost Patagonia (Novas et al, 2007). A very recent global review showed that sites with low aboveground net primary productivity (ANPP), likely as a result of water shortage, presented higher probability of populations with no-endophyte or low incidence of endophytes compared with sites with high ANPP (Semmartin et al, 2014). In addition, is worth mentioning that studies that experimentally addressed the hypothesis of improved tolerance to drought mediated by endophytes have been carried out with the mesophytic species tall fescue and perennial ryegrass exposed to water shortage for short periods of time (Saikkonen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The idea of positive effects of endophytes on plant tolerance to drought has been used to explain ecological patterns in which high symbiosis incidence is associated with low levels of precipitation (Lewis et al, 1997;Malinowski and Belesky, 2006;Afkhami et al, 2014). However, a recent global survey of endophyte incidence including a larger number of grass and fungal endophyte species in a wider environmental gradient revealed a different pattern (Semmartin et al, 2015). By reviewing the literature and adding information to the drier extreme of the gradient, they found a positive relationship between endophyte incidence and mean aboveground net primary productivity (ANPP), a variable closely associated with mean precipitation (Sala et al, 1988).…”
mentioning
confidence: 99%
“…Mean annual precipitation of the distributional range for B. setifolius and H. comosum is 259 and 471 mm, respectively, while for L. perenne and S. phoenix is 592 and 685 mm (data took from Semmartin et al, 2014, andCasas et al, 2015). Thus, it seems that the negative relationship between endophyte incidence and parameters of environmental quality (e.g., precipitation or ANPP) would be not valid in arid ecosystems (see Semmartin et al, 2015) or, at least, would be specific to species and/or ecosystems.…”
mentioning
confidence: 99%
See 1 more Smart Citation